2016
DOI: 10.4103/1658-354x.169469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perineural administration of dexmedetomidine in combination with bupivacaine in a femoral-sciatic nerve block

Abstract: Background and Aim:Perineural administration of dexmedetomidine, a α2-adrenoceptor agonist, prolongs the duration of analgesia. We hypothesized that adding dexmedetomidine to bupivacaine would prolong postoperative analgesia after below knee surgery.Materials and Methods:After ethical approval, 60 patients scheduled for below knee surgery under combined femoral-sciatic nerve block were randomly allocated into two groups to have their block performed using bupivacaine 0.5% alone (group B) or bupivacaine 0.5% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 22 publications
1
15
1
1
Order By: Relevance
“…The results of our study are in agreement with Helal [14] and his colleagues, who assessed the effects of perineural administration of dexmedetomidine in combination with bupivacaine in a femoral-sciatic nerve block, and they demonstrated that sensory and motor block onset times were shorter by 20% in dexmedetomidine group than in bupivacaine group. In addition to shorter onset time, sensory and motor blockade durations were longer in group BD (+45% and +40%, respectively) than in group B and duration of analgesia was also become longer in group BD by 75% than in group B.…”
Section: Time Of Measurementsupporting
confidence: 92%
“…The results of our study are in agreement with Helal [14] and his colleagues, who assessed the effects of perineural administration of dexmedetomidine in combination with bupivacaine in a femoral-sciatic nerve block, and they demonstrated that sensory and motor block onset times were shorter by 20% in dexmedetomidine group than in bupivacaine group. In addition to shorter onset time, sensory and motor blockade durations were longer in group BD (+45% and +40%, respectively) than in group B and duration of analgesia was also become longer in group BD by 75% than in group B.…”
Section: Time Of Measurementsupporting
confidence: 92%
“…In cases of brachial plexus blockade, the addition of DEX to the local anesthetic provided more rapid onset and longer duration of sensory and motor block with better postoperative analgesia [28]. The same effects were reported when DEX 100 μg was added to bupivacaine during ultrasound-guided combined femoral and sciatic block for below knee surgery [29].…”
Section: Discussionmentioning
confidence: 84%
“…In human studies, a dexmedetomidine-lidocaine mixture has been used to provide Bier's block and was shown to improve the quality of anesthesia, decrease tourniquet pain and reduce postoperative analgesic requirement [20]. Helal et al also demonstrated that the addition of dexmedetomidine to bupivacaine in a combined sciatic-femoral nerve block improved the analgesic effect but found significant bradycardia and hypotension in their patients requiring treatment [21]. Most authors have similarly reported (using 100 µg dexmedetomidine) side effects of dexmedetomidine such as hypertension, hypotension, bradycardia or hyperglycemia [22,23].…”
Section: Discussionmentioning
confidence: 99%